KEDUDUKAN PERJANJIAN LISAN YANG MENJADI DASAR BATALNYA AKTA PENGIKATAN JUAL BELI (ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR : 1660K/PDT/2014) - M HAFIS RAMADHAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Hasim Purba, SH, MHum2.  Dr. Dedi Harianto, SH, MHum3.  Dr. T. Keizerina Devi A, SH, CN, MHumA spoken agreement used the ground of the relationship between parties, in which they have made a mutual agreement, in accordance with the prevailing laws and regulations is stated to be legally valid, but it has soft legal force in the court because it does not have any written evidence, so when it is claimed to the court, it cannot provide evidence. All parties in the court shall present some proof such as: evidence, witness, presumption, confession, and an oath. A spoken agreement can annul an authentic deed of the sale and purchase contract when it does not meet the subjective requirements, the heirs have not obtained a renewed permit as the holder of the land use. Thus; the concerned person can renew the permit use the land by submitting an application to the Mayor or regional authorities. A land use holder is prohibited to transfer the land use permit to another party without firstly obtaining a written notice.Keywords: Spoken Agreement, Legal Force, Certificate